An evaluation of Greene's resource theory of party dominance with reference to the South African case - Balt, Laurent (Department of Political Studies, 2021)
The African National Congress is commonly thought of as a dominant party, which poses an explanatory problem – how and why is it dominant? Greene (2007) proposes that orthodox electoral market explanations fail to explain the persistence of dominant parties, and advances that “hyperincumbency advantages” (i.e. resource and policy advantages accruing to the dominant party) best explain how dominant parties persist, and that the decline in these advantages is linked with decline in party dominance. Greene's early analyses took place before the ANC qualified as a dominant party in his model: this dissertation seeks to explain whether his theory explained the ANC's party dominance and its declining electoral and ideological dominance. Methodologically, a theory-testing case study incorporating process-tracing approach is taken. The ANC's hyperincumbency advantages are described through case studies of the party's funding mechanisms, its relations with public resources, and a specific study of patronage within the ANC during Jacob Zuma's presidency. This dissertation finds that Greene's hyperincumbency approach was insufficient to accurately explain the ANC's dominance or its decline. Firstly, the ANC's electoral and ideological declined even as its access to public resources through what Greene terms a “national patronage system” increased. Secondly, the expansion of the aggregate opposition vote has been mostly due to splits off the ANC and declining partisan alignment with the party, rather than declining resource imbalances. An historical analysis of factionalism within the ANC since 1994 is undertaken. Factional dynamics within the ANC have proven important to party dominance, as the direction of patronage became primarily targeted at winning intra-party battles, and lack of factional management repeatedly caused damaging splits off the ANC. This thesis suggests that approaches to dominant party studies should consider the importance of factional management in maintaining party dominance, as a necessary but potentially insufficient condition.